Aspectos estruturais e eletrônicos de soluções sólidas KNb(1-X)TaXO3 por DFT - Silva, Jerônimo Ferreira (2020)
The evolution of computational methods applied to chemistry coupled with the advancement of calculation capacity are gaining more and more space within laboratories. Currently, it is already possible to simulate a large number of properties of a material with excellent computational accuracy / cost. One of the main responsible for this advance is the method based on Density Functional Theory (DFT), which allows the calculation of solid properties, which are difficult to synthesize or even inaccessible by experimental means. The use of such resources allows to investigate in detail the electronic structure of complex systems, such as metallic alloys and solid solutions, among others. In this work, this method was applied to investigate the electronic, structural and thermodynamic properties of the solid KNb(1-X)TaXO3 solution (with X = 0; 0.25; 0.5; 0.75 and 1), with the purpose of understand important photocatalysis properties. The study of the KNbO3 and KTaO3 isomorphs was carried out and all symmetrically irreducible configurations, for the compositions in question, were evaluated, identifying the lowest energy organizations. Structural models were proposed for the mixtures and their properties were evaluated. It was identified that each proposed model was in agreement with the experimental and theoretical data available in the literature and its spatial groups were determined, observing that greater organization of the system occurs with the increase in the proportion of tantalum. The modification of the electronic structure with the composition showed that a combination of factors, such as the value and nature of the band gap, mass and mobility of the charge carriers and structural organization can influence the photocatalytic activity observed in the different compositions of the mixtures, contributing to understanding of photocatalysis data, found experimentally, for this system.